Nutritional aspects of corn due to cover crops, nitrogen doses and inoculation with Azospirillum brasilense - Portugal, José Roberto [UNESP]; Arf, Orivaldo [UNESP]; Peres, Amanda Ribeiro [UNESP]; Meirelles, Flávia Constantino [UNESP]; Ferreira Rodrigues, Ricardo Antônio [UNESP]; Gonzaga, Alex Rangel [UNESP]; Siviero Garcia, Nayara Fernanda [UNESP]; Corsini, Daiene Camila Dias Chaves [UNESP] (Southern Cross Publishing, 2018)
In modern agriculture, there is a challenge for adequately nourishing plants using sustainable techniques, mitigating the use of mineral fertilizers, especially nitrogenous fertilizers, which are the most used for corn crops. The objective of this study is to evaluate the accumulation potential of nitrogen, phosphorus and potassium in: a) cover crops (millet, crotalaria, pigeon pea, millet + crotalaria, millet + pigeon pea and fallow) and b) corn plants sown in succession to the cover crops and with application of nitrogen doses (0, 40, 80 and 120 kg ha-1) in topdressing and inoculation via seeds using Azospirillum brasilense. The experiment comprised randomized blocks in a 6 × 4 × 2 factorial design totaling 48 treatments and 4 replications. The study was conducted at the Experimental Farm of the Faculty of Engineering (UNESP), Ilha Solteira campus, located in the municipality of Selvíria, Mato Grosso do Sul (MS) state. The soil of the site is a typical clayey dystrophic Red Latosol. The millet + crotalaria intercropping allows the accumulation of high amounts of N and K and results in a great accumulation of dry matter and nutrients in corn plants sown in succession. Application of nitrogen in topdressing provided an increase in the accumulated dry matter of corn plants of up to 85 kg ha-1. Inoculation via seeds using Azospirillum brasilense did not increase the accumulation of dry matter and nutrients of corn plants. It is recommended to cultivate corn in succession to the millet + crotalaria and the aplication of 80 to 100 kg ha-1 of N in topdressing aiming at better nutrition of the plants.
Keywords: Diazotrophic bacteria; Green manure; Nitrogen; Plant nutrition; Zea Mays L.